2003
DOI: 10.1177/0734904103035393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intumescent Coatings for Shipboard Fire Protection

Abstract: In response to several claims from Manufacturers that intumescent coatings could be used in place of fire insulation and provide equal protection to shipboard structures during a fire, U.S. Navy conducted an extensive investigation of several fire protective coatings for use aboard ship. These fire protective coatings included water and solvent based coatings, insulative coatings, and foams. The objective of this program was to identify passive fire protection (PFP) coatings for shipboard interior applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…For instance, in structural polymer composites, the use of intumescent coatings is being developed for the thermal protection and thermo-mechanical stabilization of the composites. An early example of the use of several commercial intumescent coatings for the protection of glass-reinforced vinyl ester resin/ balsa wood core sandwich composites was reported by Sorathia et al for military applications [11]. In this paper, small scale fire tests demonstrated a significant reduction of flame spread and smoke density when applied over composites substrates.…”
Section: Intumescent Coatingsmentioning
confidence: 85%
“…For instance, in structural polymer composites, the use of intumescent coatings is being developed for the thermal protection and thermo-mechanical stabilization of the composites. An early example of the use of several commercial intumescent coatings for the protection of glass-reinforced vinyl ester resin/ balsa wood core sandwich composites was reported by Sorathia et al for military applications [11]. In this paper, small scale fire tests demonstrated a significant reduction of flame spread and smoke density when applied over composites substrates.…”
Section: Intumescent Coatingsmentioning
confidence: 85%
“…One of the greatest impediments to the development and application of polyureas in the design and construction of military facilities is their relatively high flammability and their susceptibility to degradation due to exposure to elevated temperatures caused by fire [10], [11], [12] and [13]. One effective way to flame retard polyurea is to use an intumescent system.…”
Section: Introductionmentioning
confidence: 99%
“…Intumescent coatings are sometimes applied to steel structural members to achieve the fire resistance ratings required by building codes, although the US Navy has concluded that intumescent coatings do not provide a level of fire resistance equivalent to traditional insulation, largely due to poor adhesion characteristics [89]. In addition to being applied as a coating, intumescents are sometimes grafted into composite materials to improve fire performance.…”
Section: Comprehensive Pyrolysis Models: Intumescent Coatingsmentioning
confidence: 99%